Charge and Press machine at Hercules Port Ewen plant - Hercules Incorporated (1945)
Close-up view of the Charge and Press machine used to fill shells with an explosives charge the Hercules Powder Company plant in Port Ewen, New York. After the charge was pressed into the bottom of the shells, the shells were sent to the Filling Room, where wired plugs were inserted before the shells were packed for shipment. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) specialized in the manufacture of explosives and smokeless powders. During World War II, the company's Port Ewen plant produced a range of special detonators designed for military use.
Keywords: Explosives, Military; Detonators; Chemical industry; Propellants; Hercules Incorporated; World War (1939-1945); Military supplies; Corporations; Explosives; Defense industries; Machinery